The Updating Status in Facebook: The Interference of English among Users in Academic Context - Roslina Roslina; Nurhayati Nurhayati (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
This study investigates the interference of English use made by Facebook users in writing status on their account. The researchers formulated two research questions: 1) what types of interferences are found on Facebook status; 2) what factors cause interference on Facebook status. The purpose of this study is to find out the interferences and the factors that cause the interference. This research uses descriptive qualitative method. The descriptive qualitative was used to elaborate, describe and disclose kinds of interference and also the factors of interference that Facebook users produced in updating status. The research showed that the way of the Facebook users in transferring their source language to target language tends to be negative transfer or it is called as language interference. The negative transfers made by Facebook users are semantic and grammatical interference. While, the factors that cause the interference are bilingualism background, disloyalty target language, limited vocabularies of TL mastered by a learner, prestige and style, interlingual factor, overextension of analogy, and transfer of structure.